REGULASI EMOSI DAN DINAMIKA INTERAKSI SOSIAL DALAM PERILAKU MARAH ANAK USIA DINI: STUDI KASUS DI TAMAN KANAK-KANAK - Muslimah, Inayah Fatha; Wardhani, Raden Roro Dina Kusuma; Aprilyanti, Dian Surya (Departemen Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2026)
This study aims to describe angry behavior in children aged 4–5 years in Group A at Yasiba Kindergarten in Kramatwatu, Serang Regency, and to identify the triggering factors, forms of behavior, and strategies used by teachers in dealing with such behavior. This study uses a qualitative approach with a case study method. Data collection techniques included interviews, observations, and documentation. The research subjects consisted of a child with the initials Tn and a classroom teacher with the initials GK. The results of the study showed that Tn's angry behavior tended to arise when interacting with peers, especially when social conflicts occurred such as taking toys or interference from friends. The forms of behavior displayed include throwing toys, crying, and screaming with a frequency of about twice a week. The factors that trigger angry behavior include the ability to regulate emotions that has not developed optimally, limited experience of socializing in the family environment, and the dynamics of social interaction at school. Teachers implement various management strategies, such as a personalized approach, persuasive advice, educational consequences, and activity diversion. Additionally, school support through role-playing activities and intensive communication with parents contributes to the child's gradual emotional development. This study emphasizes the importance of collaboration between teachers and families in supporting the development of emotional regulation in young children.